2007
DOI: 10.1128/jb.00206-07
|View full text |Cite
|
Sign up to set email alerts
|

Microcin J25 Has Dual and Independent Mechanisms of Action inEscherichia coli: RNA Polymerase Inhibition and Increased Superoxide Production

Abstract: Microcin J25 (MccJ25) uptake by Escherichia coli requires the outer membrane receptor FhuA and the inner membrane proteins TonB, ExbD, ExbB, and SbmA. MccJ25 appears to have two intracellular targets: (i) RNA polymerase (RNAP), which has been described in E. coli and Salmonella enterica serovars, and (ii) the respiratory chain, reported only in S. enterica serovars. In the current study, it is shown that the observed difference between the actions of microcin on the respiratory chain in E. coli and S. enterica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
76
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 56 publications
(57 reference statements)
3
76
0
Order By: Relevance
“…Thus, MccJ25 would inhibit transcription by clogging the conduit, thereby blocking the access of the substrates to the active center (1,25). Recently, we have found that in E. coli cells overproducing the microcin receptor, FhuA, the antibiotic also targets the respiratory chain and inhibits cell respiration (5). Although the mechanistic details of this action have yet to be defined, it seems to result from an increased superoxide production.…”
mentioning
confidence: 99%
“…Thus, MccJ25 would inhibit transcription by clogging the conduit, thereby blocking the access of the substrates to the active center (1,25). Recently, we have found that in E. coli cells overproducing the microcin receptor, FhuA, the antibiotic also targets the respiratory chain and inhibits cell respiration (5). Although the mechanistic details of this action have yet to be defined, it seems to result from an increased superoxide production.…”
mentioning
confidence: 99%
“…Additionally, the inner membrane protein SbmA transports MccJ25 from the periplasmic to the cytoplasmic space (13). Once inside the sensitive cell, the peptide is able to inhibit E. coli RNA polymerase (RNAP) and membrane respiratory chain, which represent the MccJ25 targets (2,5,7,18). Several Salmonella enterica serovars showed high sensitivity against MccJ25, while others, like Salmonella enterica serovar Typhimurium, S. enterica serovar Derby, and some S. enterica serovar Enteritidis strains were completely resistant (16).…”
mentioning
confidence: 99%
“…MccJ25 is active on gram-negative bacteria related to the producer strain, and among them are several human pathogens (11,12,16). It was previously shown that the E. coli RNA polymerase (5,18) and the bacterial respiratory chain (2,9) are the targets for MccJ25 action. MccJ25 is active on pathogenic strains of Salmonella spp., Shigella spp.…”
mentioning
confidence: 99%